Relative Effectiveness of Guided Inquiry and Demontration Methods on Students Performance in Practical Chemistry in Secondary Schools in Osun State, Nigeria - E.F., Bamidele (Advances in Social Sciences Research Journal, 2015)
The paper investigated the relative effectiveness of Guided Inquiry Strategy and Demonstration Method on the performance of students in practical Chemistry in the secondary schools in Osun State, Nigeria. The study also examined the effects of these methods on the retention ability of the students. The study adopted the non-equivalent pre-test, post-test, control group experimental design. There were two groups; the Guided Inquiry Strategy (GIS) group and the Demonstration Teaching Method (DTM) group. The population for the study consists of all Chemistry students in Senior Secondary School two (SSSII) in Ifelodun Local Government Area, of the state. The study sample was made up of seventy eight Chemistry students in Senior Secondary School two (SSSII) in their intact classes in two public co-educational Secondary Schools randomly selected in Ifelodun Local Government Area. The instrument used for the study was Achievement Test in Qualitative Analysis (ATQA). This was used for the pre-test, post-test and retention ability test of the students in qualitative analysis. Results showed that there was a significant difference in the students’ performance after exposure to the treatment (t = 62.712; p = 0.000). Also, students taught with the GIS performed significantly better than those that were taught with the DTM (t = 27.46; p = 0.000). The mean scores 23.52 and 11.00 for the GIS and DTM respectively). There was also a significant difference in the retention ability of the two groups (t = 13.047; p = 0.000), with the GIS group having better retention ability of the concept taught. It was thus concluded that Guided Inquiry Strategy is a very good teaching strategy for practical chemistry because it enhanced the performance and retention of learning.